Intervention proposal for the development of Emotional Intelligence in children living in social risk and vulnerability - Sánchez Gómez, Martín (2021)
The influence between social vulnerability and emotional states has been researched, and results have demonstrated that it may have negative consequences especially for young population. In addition to this, different studies conclude that emotional intelligence may play an important part in reducing the risk factors of social vulnerability. The main objective of this paper is to create a program to develop emotional abilities in children between 6 and 12 years old, that live in risk of social exclusion and social vulnerability. This program is carried our throughout 13 sessions of 90 minutes each. The main contents that are included in the program are the key components of Emotional Intelligence proposed in the theoretical model of Mayer and Salovey: perception and expression of emotions, emotional facilitation, understanding and analyzing emotions, and regulation of emotions. Finally, a way to evaluate the impact of the program is proposed. Besides the work done, many advances are still needed to be made to improve the situation of risk and social vulnerability in this group population.